Direct and Structural Discrimination in Contests - Yosef Mealem; Shmuel Nitzan (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper evaluates direct and structural discrimination as a means of increasing efforts in the most widely studied contests. We establish that a designer who maximizes efforts subject to a balanced-budget constraint prefers dual discrimination, namely, change of the contestants' prize valuations as well as bias of the impact of their efforts. Optimal twofold discrimination is often superior to any single mode of discrimination under any logit CSF. Our main result establishes that, surprisingly, from the designer's point of view, dual discrimination can yield the maximal possible efforts when it is applied to the prototypical simple logit CSF. In this case it yields almost the highest valuation of the contested prize.
Keywords: D70; D72; D74; D78; 330; contest design; balanced-budget-constraint; direct discrimination; structural discrimination; extreme dual discrimination; contest success function